Hybrid Phosphine/Amino‐Acid Ligands Built on Phenyl and Ferrocenyl Platforms: Application in the Suzuki Coupling of o‐Dibromobenzene with Fluorophenylboronic Acid. Issue 1 (12th January 2023) - Radal, Léa; Almallah, Hamze; Labonde, Marine; Roger, Julien; Cattey, Hélène; Sabbadin, Henri; Amardeil, Régine; Pirio, Nadine; Hierso, Jean‐Cyrille
Abstract: We describe the synthesis and characterization of two classes of hybrid phosphino ligands functionalized with amino ester or amino acid groups. These compounds are built either on a rigid planar phenyl platform or on a functionalized – conformationally controlled – rotational ferrocene backbone. Modifications at the −PR2 phosphino groups (R=aryl and alkyl, with various steric bulk, Ph, Mes, i ‐Pr, Cy) and at the amino acid/amino ester functions are reported, showing a valuable high modularity. The coordination chemistry of these compounds regarding palladium and gold was investigated, in particular with respect to the coordination mode of the phosphino groups and the preferred interaction with metals for the amino ester and amino acid functions. For all the hybrid ligands, based either on ferrocenyl or phenyl platforms, the (P, N)‐chelating effect dominates in solution for coordination to Pd(II), while linear P−Au(I) complexes without interaction with the amino groups are assumed. The investigation of the catalytic activity of these new ligands in the demanding palladium‐catalyzed Suzuki–Miyaura coupling of o ‐dibromoarenes with fluorophenylboronic acid underlined the importance of the amino ester dicyclohexylphosphinoferrocene for avoiding the deleterious homocoupling and arene oligomerization side‐reactions that were otherwise observed with the other phosphine ligands. Abstract : Hybrid 1‐amino ester‐ or 1‐amino acid‐1′‐phosphinoferrocenes and some corresponding 1, 2‐amino ester‐phosphinobenzenes were synthesized from reductive amination of carbonyl precursors. Their coordination modes to Pd(II) and Au(I) are reported, and the superior activity of a dicyclohexylphosphinoferrocene amino ester in a challenging Suzuki coupling of dihaloarenes is illustrated.